HYDROTHERMAL GOLD MINERALIZATION AT THE RODNIKOVOE DEPOSIT IN SOUTH KAMCHATKA, RUSSIA - Takahashi R.; Matsueda H.; Okrugin V.M. (My University, 2002)
The Rodnikovoe gold deposit situated in a presently active hydrothermal system located north of the Mutnovsko-Asachinskaya geothermal area in southern Kamchatka, Far Eastern Russia, consists of typical low-sulfidation quartz-adularia veins in a host rock of diorite. The age of the mineralization was dated by the K-Ar method as 0.9 to 1.1 Ma based on adular-ia collected from the veins. Representative ore minerals in the deposit are electrum, argentite, aguilarite, polybasite, pearceite and lenaite. Dominant alteration minerals are adularia, α-cristobalite, chlorite, illite and kaolinite. Hydrothermal solutions of neutral pH were responsible for the mineralization, which is divided into six stages defined by tectonic boundaries. Gold mineralization occurred in stages I and III. Hydrothermal brecciation occurred during stages III, IV and VI. Stages II, IV, V and VI were barren. The estimated ore formation temperature based on a fluid inclusion study is 150 to 250 °C at a depth of approximately 170 m below the paleo-water table. Boiling of hydrothermal fluids is hypothesized as the cause of the intermittent deposition of gold ore. The sulfur and oxygen fugacities during the deposition of anhydrite prior to the hydrothermal brecciation were higher than those during the gold mineralization stages. The occurrence in the hydrothermal breccia of fragments of high grade Au-Ag and polymetallic ores suggests that higher grade mineralization of these metal ores might have occurred in a deeper portion of the deposit.
Keywords: epithermal gold mineralization; boiling; hydrothermal brecciation; electrum; K-Ar age; fluid inclusion; physico-chemical condition; Rodnikovoe; Kamchatka; Russia